200 MeV Ag15+ swift heavy ion beam induced property modifications in Nb2O5 thin films by fluence variation. (December 2019) - Rathika, R.; Kovendhan, M.; Joseph, D. Paul; Vijayarangamuthu, K.; Kumar, A. Sendil; Venkateswaran, C.; Asokan, K.; Jeyakumar, S. Johnson
Abstract: Swift Heavy Ion beam irradiation is capable of inducing a variety of modifications on the properties of thin films by high energy deposition. The Nb2 O5 thin films deposited by spray pyrolysis technique were then irradiated with 200 MeV Ag 15+ ions at fluence ranging from 5 × 10 11 to 1 × 10 13 ions/cm 2 . The thickness of the deposited film was 308 nm and the irradiated area was 1x1 cm 2 . The XRD pattern of the pristine film confirmed the tetragonal structure of Nb2 O5 . Upon irradiation, peak intensity decreased significantly and some peaks vanished due to irradiation induced defects. The subtle Raman peaks around 960, 223, and 126 cm −1 corresponds to edge shared octahedra, T2u mode and Nb–Nb vibration respectively. After irradiation, complete suppression of vibration modes was observed except for 1 × 10 12 fluence. For the 1 × 10 12 ions/cm 2 fluence, Raman modes reappear with increased intensity due to irradiation induced recrystallization. Optical transmittance spectra showed a decreased trend as fluence increased due to the formation of optically absorbing centers. Both the direct and indirect band gaps showed a systematic red shift. The pristine AFM image revealed agglomeration of particles while a network like structure was observed after irradiation. Results of transport properties studied for both pristine and irradiated films at room temperature by Hall effect are also presented. Highlights: Nb2 O5 film retained its tetragonal structure even after irradiation. Increased Raman intensity for 1 × 10 12 ions/cm 2 fluence indicates irradiation induced recrystallization. Red shift was observed in both the direct and indirect band gaps. AFM revealed unique porous network morphology of Nb2 O5 . Maximum conductivity observed for 1 × 10 12 ions/cm 2 fluence by domination of band gap reduction over grain size.